Progress and prospect of carbon dioxide capture, utilization and storage in CNPC oilfields - Xinmin SONG; Feng WANG; Desheng MA; Ming GAO; Yunhai ZHANG (Petroleum Exploration and Development, 2023)
The development history of carbon capture, utilization and storage for enhanced oil recovery (CCUS-EOR) in China is comprehensively reviewed, which consists of three stages: research and exploration, field test and industrial application. The breakthrough understanding of CO2 flooding mechanism and field practice in recent years and the corresponding supporting technical achievements of CCUS-EOR project are systematically described. The future development prospects are also pointed out. After nearly 60 years of exploration, the theory of CO2 flooding and storage suitable for continental sedimentary reservoirs in China has been innovatively developed. It is suggested that C7–C15 are also important components affecting miscibility of CO2 and crude oil. The mechanism of rapid recovery of formation energy by CO2 and significant improvement of block productivity and recovery factor has been verified in field tests. The CCUS-EOR reservoir engineering design technology for continental sedimentary reservoir is established. The technology of reservoir engineering parameter design and well spacing optimization has been developed, which focuses on maintaining miscibility to improve oil displacement efficiency and uniform displacement to improve sweep efficiency. The technology of CO2 capture, injection and production process, whole-system anticorrosion, storage monitoring and other whole-process supporting technologies have been initially formed. In order to realize the efficient utilization and permanent storage of CO2, it is necessary to take the oil reservoir in the oil-water transition zone into consideration, realize the large-scale CO2 flooding and storage in the area from single reservoir to the overall structural control system. The oil reservoir in the oil-water transition zone is developed by stable gravity flooding of injecting CO2 from structural highs. The research on the storage technology such as the conversion of residual oil and CO2 into methane needs to be carried out.